Analysis Of The Management Of Education Unit Operational Assistance Fund (BOSP) At Public Elementary School 02 Tanjung Sakti Pumu Lahat District - Elanda, Tara; Anggriani , Ida; Subhi , Ramadan (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The aim of the research is to analyze the management of educational unit operational assistance funds (BOSP) at SD Negeri 02 Tanjung Sakti Pumu, Lahat Regency. This research approach is qualitative research. The data collection methods used in this research are interview techniques, documentation techniques and observation techniques. The location of this research is SD Negeri 02 Tanjung Sakti Pumu, Lahat district.The results of the research show that the comparison of BOSP Technical Instructions for implementation and accountability is appropriate and for planning regarding the preparation of RKAS documents carried out through RKAS document preparation meetings involving members of the education unit and school committees, it is not in accordance with the provisions of the Minister of Education, Culture and Research and Technology. Efficiency of managing BOSP funds at State Elementary School 02 Tanjung Sakti Pumu, Lahat Regency, in 2021-2023, spending with an average ratio of 100% is said to be less efficient and for the effectiveness of BOSP fund management at SD Negeri 02 Tanjung Sakti Pumu, Lahat Regency. In 2021-2023, it can be seen that the school is able to realize budget management. BOSP funds with a very effective level of 100%.